1992
DOI: 10.1093/clinids/15.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Antimicrobial Resistance of Clinical Isolates of Streptococcus pneumoniae in Bellvitge Hospital, Barcelona, Spain (1979-1990)

Abstract: From January 1979 to December 1990 we studied the susceptibility of 1,492 pneumococcal strains isolated from adult patients in Bellvitge Hospital, Barcelona, Spain, to nine antimicrobial agents. Among clinically significant pneumococci, the incidence of penicillin-resistant strains increased from 4.3% in 1979 to 40% in 1990, and that of erythromycin-resistant strains also rose from 0% in 1979 to 9.4% in 1990. On the other hand, the incidence of strains resistant to tetracycline decreased from 76.1% to 37.6%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
126
0
20

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(160 citation statements)
references
References 20 publications
14
126
0
20
Order By: Relevance
“…Many studies [7,8,14,29,30] have reported an increase in the prevalence of antibiotic resistance of laboratory isolates in the last 20 years. These studies fail to address the prevalence of antibiotic-resistant pneumococci in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies [7,8,14,29,30] have reported an increase in the prevalence of antibiotic resistance of laboratory isolates in the last 20 years. These studies fail to address the prevalence of antibiotic-resistant pneumococci in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Early resistant isolates showed intermediate levels of resistance to penicillin (minimum inhibitory concentration (MIC) 0n12-1 µg\ml) but later, highly resistant isolates (MIC 4-8 µg\ml) [5], and multiply-resistant pneumococci were reported [6]. Reports show a progressive increase in prevalence once resistant strains are introduced into an area, as observed in Spain between 1980 and 1987 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Uma nova cepa de Staphylococcus aureus resistente à meticilina, adquirida na comunidade, tem sido descrita 78 , com propriedades diferentes das cepas adquiridas no hospital com esta caracterís-tica. A prevalência de microrganismos resistentes aos macrolídeos [79][80][81] e cefalosporinas 82 tem aumentado nas regiões com grande utilização de macrolídeos. Em geral, o planejamento da terapêutica antimicrobiana não deve ser baseado apenas no conhecimento do organismo mais provável numa determinada faixa etária e na gravidade da doença, mas também com informações acerca dos padrões locais de resistência aos antimicrobianos.…”
Section: Padrões De Resistência Aos Antimicrobianosunclassified
“…La tasas mas altas de prevalencia han sido reportadas en España (40 -53%), Nueva Guinea (33%) y países de Africa del Sur (28 -62%), (2,4,5,6). …”
Section: Introductionunclassified